Approximating Incoherent Monochromatic Light Sources in FDTD Simulations - Metzner, Dominik; Potthoff, Jens; Zentgraf, Thomas; Förstner, Jens (Photonics)
Light-emitting diodes (LEDs) are becoming increasingly important across various sectors of the lighting industry and are being used more frequently. In the field of symbolic projection, research is increasingly focusing on implementing light modulation using energy-efficient, incoherent LEDs rather than lasers. Since light modulation in micro- and nano-optics is typically achieved through phase modulation, Finite-Difference Time-Domain (FDTD) simulations are employed for analysis. The objective of this article is to investigate different approaches for approximating incoherent monochromatic light sources within FDTD simulations. To this end, two approaches based on dipole sources are considered, as well as a method involving plane waves with modulated wavefronts based on Cosine–Fourier functions and a method based on the superposition of Gaussian beams. These methods are evaluated in terms of their accuracy using a two-dimensional double-slit configuration and are compared against a fully incoherent analytical reference.
Keywords: tet_topic_opticalantenna; tet_topic_numerics; tet_topic_meta

Polar discontinuities, emergent conductivity, and critical twist-angle-dependent behaviour at wafer-bonded ferroelectric interfaces - Rogers, Andrew; Holsgrove, Kristina; Schäfer, Nils A.; Koppitz, Boris; McCluskey, Conor J.; Yedama, Shivani; Lynch, Ronan; Sloan, Keelan; Porter, Barry; Sykes, Adam; Catalan Daniels, Alex; Silva, Romualdo S.; et al. (Nature Communications)
Probing novel properties, arising from twisted interfaces, has traditionally relied on the stacking of exfoliated two-dimensional materials and the spontaneous formation of van der Waals bonds. So far, investigations involving intimate covalent or ionic bonds have not been a focus. Yet, we show here that an established technique, involving thermocompressional wafer bonding, works well for creating twisted non-van der Waals interfaces. We have successfully bonded z-cut lithium niobate single crystals to create ferroelectric oxide interfaces with strong polar discontinuities and have mapped the associated emergent interfacial conductivity. In some instances, a dramatic change in microstructure occurs, involving local dipolar switching. A twist-induced collapse in the capability of the system to effec8tively screen interfacial bound charge is implied. Importantly, this only occurs around specific moiré twist angles with sparse coincident lattices and associated short-range aperiodicity. In quasicrystals, aperiodicity is known to induce pseudo-bandgaps and we suspect a similar phenomenon here.

Integrating an Organocatalyst into a Polymeric Gel Framework for the Continuous Microflow Baylis–Hillman Reaction - Killi, Naresh; Kumar, Amit; Nebhani, Leena; Obst, Franziska; Richter, Andreas; Reineke Matsudo, Bernhard; Zentgraf, Thomas; Kuckling, Dirk (ACS Omega)
Continuous flow catalysis utilizing gel-bound organocatalysts within a microfluidic reactor represents a compelling strategy in the realm of organic synthesis. In this study, a quinuclidine-based catalytic monomer (QMA) was synthesized to create polymer gel dots through the process of photopolymerization that serve as a support for the catalyst. The resulting gel-bound organocatalysts were assembled within a continuous microfluidic reactor to facilitate the Baylis–Hillman reaction between various aldehydes and acrylonitrile at a temperature of 50 °C. The conversion of the product was assessed using 1H NMR spectroscopy as an offline analytical method over a duration of 8 h. The findings indicated that highly reactive aldehydes achieved conversion rates exceeding 90%, in contrast to their less reactive counterparts. Furthermore, these results were juxtaposed with previously published data derived from alternative synthetic methodologies, revealing that the continuous microfluidic reactions employing integrated organocatalysts within polymer networks exhibited significantly higher conversions with reduced reaction times (8 h) at the same temperature (50 °C). Additionally, the influence of different geometries (round, triangular, and square) of the gel dots on catalytic activity was investigated, with round and square gel dots demonstrating slightly superior performance compared with triangular gel dots, attributed to their increased surface area. Moreover, an extended reaction period of 6 days was conducted using 4-bromobenzaldehyde and acrylonitrile, resulting in a conversion rate exceeding 70%, which remained stable for 5 days before experiencing a slight decline due to product accumulation on the gel dots.

Independent Wavefront Multiplexing with Metasurfaces via Non‐Injective Transformation - Jin, Xiao; Zentgraf, Thomas (Advanced Materials)
Abstract Metasurface holography offers a powerful approach for manipulating wavefronts at the nano and micro scale. Extensive research has been conducted to enhance the multiplexing capacity for diverse wavefronts. However, the independence of multiplexed channels is fundamentally restricted in techniques using single‐layer metasurfaces, resulting in unavoidable crosstalk and the need for post‐filtering of the output wavefronts. Here, a universal wavefront multiplexing concept is presented based on non‐injective transformation. By employing joint optimization on two metasurfaces, different channels can be independently designed without any constraints on the output wavefronts. To validate this approach, ultra‐compact orbital angular momentum (OAM) sorters are designed. In these experiments, the output beams from different channels can be independently mapped to 2D positions with high fineness. In another application of wavefront‐multiplexed holography, 10‐channel multiplexing is experimentally achieved with minimal crosstalk and without the need for post‐processing. These results demonstrate the independence between channels enabled by the non‐injective transformation in the method. The precise wavefront control and high multiplexing capacity underscore its potential for scalable wavefront manipulation devices.

Increasing the design degree of freedom for polarization through multilayer synchronous polarization projection - Jin, Xiao; Zentgraf, Thomas (Advanced Photonics)
The degrees of freedom (DoFs) of light determine the maximum number of independent signal channels an optical system can support. However, the polarization DoF is intrinsically limited to two by orthogonality, which causes unavoidable crosstalk and often forces position multiplexing, where different channels are assigned to distinct spatial locations to suppress crosstalk. This research introduces a multilayer synchronous polarization projection method that fundamentally increases the DoF for polarization multiplexing. The DoF equals twice the number of projection layers. We experimentally demonstrate six- channel polarization multiplexing holography without position multiplexing. The six-channel multiplexing results indicate that our approach exceeds the conventional polarization multiplexing method, yielding an average 3.79 dB improvement in extinction ratio across the six channels. Compared with the theoretical limit of traditional polarization multiplexing, our method reduces crosstalk by an average of 6.52 dB across all channels in a seven-channel design. The polarization projection method breaks the DoF limitation of polarization multiplexing, opening a path toward high-dimensional photonic information encoding for communication, encryption, and imaging.

Toward integrated sensors for optimized optical coherence tomography with undetected photons - Roeder, Franz; Pollmann, René; Quiring, Viktor; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (Physical Review Applied)
The development of practical sensors for optical coherence tomography (OCT) with undetected photons requires miniaturization via integration. To be practical, these sensors must exhibit a large spectral bandwidth and a high brightness, which are linked to a high axial resolution and a sufficient signal-to-noise ratio, respectively. Here, we combine these requirements in a scheme for OCT measurements with undetected photons based on nonlinear <a:math xmlns:a="http://www.w3.org/1998/Math/MathML" display="inline"> <a:mi>Ti</a:mi> <a:mo>:</a:mo> <a:msub> <a:mrow> <a:mi>Li</a:mi> <a:mi>Nb</a:mi> <a:mi mathvariant="normal">O</a:mi> </a:mrow> <a:mn>3</a:mn> </a:msub> </a:math> waveguides. We investigate the performance benchmarks of the commonly used SU(1,1) scheme in comparison to an induced-coherence scheme and find that the latter is actually better suited when implementing measurements with undetected photons in integrated systems. In both schemes, we perform pump-gain optimization and OCT measurements with undetected photons with an axial resolution as low as <d:math xmlns:d="http://www.w3.org/1998/Math/MathML" display="inline"> <d:mn>28</d:mn> <d:mspace width="0.2em"/> <d:mtext fontfamily="times">μ</d:mtext> <d:mrow> <d:mi mathvariant="normal">m</d:mi> </d:mrow> </d:math> .

Quantum-limited detection of the arrival time and the carrier frequency of time-dependent signals - Folge, Patrick Fabian; Serino, Laura Maria; Mišta, Ladislav; Brecht, Benjamin; Silberhorn, Christine; Řeháček, Jaroslav; Hradil, Zdeněk (Optica)
Precise measurements of both the arrival time and carrier frequency of light pulses are essential for time–frequency-encoded quantum technologies. Quantum mechanics, however, imposes fundamental limits on the simultaneous determination of these quantities. In this work, we derive and experimentally verify the quantum uncertainty bounds governing joint time–frequency measurements. We show that when detection is restricted to finite time windows, the problem is naturally described by a quantum rotor, rendering the commonly used Heisenberg uncertainty relation inapplicable. We further propose an optimal detection scheme that saturates these fundamental limits. By sampling the Q -function, we demonstrate the reconstruction of the Wigner function beyond the harmonic oscillator. Using an experimental implementation based on a quantum pulse gate, we confirm that the proposed scheme approaches the ultimate quantum limit for simultaneous time–frequency measurements. These results provide a framework for joint time–frequency detection with direct implications for precision measurements and quantum information processing.

Practical considerations for assignment of photon numbers with SNSPDs - Schapeler, Timon; Mischke, Isabell; Schlue, Fabian; Stefszky, Michael; Brecht, Benjamin; Silberhorn, Christine; Bartley, Tim (APL Quantum)
Superconducting nanowire single-photon detectors (SNSPDs) can enable photon-number resolution (PNR) based on accurate measurements of the detector’s response time to few-photon optical pulses. In this work, we investigate the impact of the optical pulse shape and duration on the accuracy of this method. We find that Gaussian temporal pulse shapes yield cleaner arrival-time histograms and, thus, more accurate PNR, compared to bandpass-filtered pulses of equal bandwidth. For low system jitter and an optical pulse duration comparable to the other jitter contributions, photon numbers can be discriminated in our system with a commercial SNSPD. At 60 ps optical pulse duration, photon-number discrimination is significantly reduced. Furthermore, we highlight the importance of using the correct arrival-time histogram model when analyzing photon-number assignment. Using exponentially modified Gaussian distributions, instead of the commonly used Gaussian distributions, we can more accurately determine photon-number misidentification probabilities. Finally, we reconstruct the positive operator-valued measures of the detector, revealing sharp features that indicate the intrinsic PNR capabilities.

Experimental entropic uncertainty relations in dimensions three to five - Serino, Laura Maria; Chesi, Giovanni; Brecht, Benjamin; Maccone, Lorenzo; Macchiavello, Chiara; Silberhorn, Christine (Physical Review A)
We provide experimental validation of tight entropic uncertainty relations for the Shannon entropies of observables with mutually unbiased eigenstates in high dimensions. In particular, we address the cases of dimensions <a:math xmlns:a="http://www.w3.org/1998/Math/MathML"> <a:mrow> <a:mi>d</a:mi> <a:mo>=</a:mo> <a:mn>3</a:mn> </a:mrow> </a:math> , 4, and 5 and consider from 2 to <b:math xmlns:b="http://www.w3.org/1998/Math/MathML"> <b:mrow> <b:mi>d</b:mi> <b:mo>+</b:mo> <b:mn>1</b:mn> </b:mrow> </b:math> mutually unbiased bases. The experiment is based on pulsed frequency bins measured with a multioutput quantum pulse gate, which can perform projective measurements on a complete high-dimensional basis in the time-frequency domain. Our results fit the theoretical predictions: the bound on the sum of the entropies is never violated and is saturated by the states that minimize the uncertainty relations.

Fabrication of uniform, high-field-enhanced plasmonic satellite clusters using multidewetting - Kim, Minjun; Devaraj, Vasanthan; Seo, Hyeon-Seok; Eom, Seongjae; Lee, Jeong-Su; Lee, Donghan; Zentgraf, Thomas; Lee, Jong-Min; Jeon, Min Yong (Quantum Sensing and Nano Electronics and Photonics XXII)

Cascaded Metasurface Interferometer for Multipath Interference with Classical and Quantum Light - Aschwanden, Rebecca; Claro-Rodríguez, Nicolás; Zhao, Ruizhe; Kallert, Patricia Anna Maria; Krieger, Tobias; Buchinger, Quirin; Covre da Silva, Saimon F.; Stroj, Sandra; Rota, Michele; Höfling, Sven; Huber-Loyola, Tobias; Rastelli, Armando; et al. (ACS Photonics)
Beamsplitters represent fundamental components in both classical and quantum optical systems, enabling the distribution of light, as well as the generation of interference, superposition, and entanglement. However, optical networks constructed from conventional bulk 2 × 2-beamsplitters encounter inherent scalability issues, as the number of required beamsplitters scales quadratically with the number of optical modes for a fully connected network. Metasurfaces offer a promising route to overcome these constraints. By manipulating light at the wavelength scale, compact optical components with advanced functionalities can be constructed, which address several modes simultaneously. In this work, we design and experimentally utilize a metasurface as a multiport beamsplitter. Furthermore, we realized a multimode interferometer composed of two cascaded metasurfaces. We characterize the individual and cascaded metasurfaces by using classical light, showing controllable splitting ratios through tunable phase relations. We then expand the approach to quantum light, employing single photons to demonstrate second- and third-order photon correlations as well as single photon interference across multiple spatial paths. These results establish metasurface-based multiport beamsplitters as a scalable and reconfigurable platform bridging classical and quantum photonics.
Keywords: metasurface; beamsplitter; interferometer; quantum network; single photons; nanophotonics

Polarization- and Wave-Vector Selective Optical Metasurface with Near-Field Coupling - Wetter, Helene; Wingenbach, Jan; Rehberg, Falk; Gao, Wenlong; Schumacher, Stefan; Zentgraf, Thomas (ACS Photonics)
Metasurfaces are powerful tools for manipulating light using small structures on the nanoscale. In most metasurfaces, near-field couplings are treated as being unfavorable perturbations. Here, we experimentally investigate a structure consisting of sinusoidally modulated silicon waveguides where near-field coupling of local resonances leads to negative coupling, i.e., a negative coupling constant. This gives rise to wave-vector-dependent eigenstates of elliptical, linear, and circular polarizations. In particular, fully circular polarization states are not only present at a single point in momentum space (k-space) but also along a line. This circular polarization line, as well as a linear polarization line, emanates from a polarization degeneracy at the Dirac point. We experimentally validate the existence of these eigenstates and demonstrate the energy-, polarization-, and wave vector dependence of this metasurface as well as its sensitivity to fabrication tolerances. By tuning the incident k-vector, certain polarization-energy eigenstates are strongly reflected, allowing for uses in angle-tunable polarization filters and light sources.
Keywords: metasurface; waveguides; Dirac point; polarization; negative coupling

A functionalization-free plasmonic hole-sphere nanogap SERS platform for reliable on-site analysis and oxide-state classification - Kim, Minjun; Heo, Damun; Cho, Sung Yoon; Lee, Ye-Won; Gu, Sun-Hwa; Adhikari, Samir; Lee, Donghan; Jeong, Seok Soon; Kim, Hyuck Soo; Devaraj, Vasanthan; Zentgraf, Thomas; Jeon, Min Yong; et al. (Nanoscale)
A functionalization-free plasmonic nanogap platform enables reliable on-site SERS based oxidation-state differentiation of arsenic through uniform metal-vacuum-metal cavities with high electromagnetic enhancement and minimal background interference.

Bridging chemistry and Gaussian boson sampling: a photonic hierarchy of approximations for molecular vibronic spectra - Eickmann, Jan-Lucas; Luo, Kai-Hong; Roiz, Mikhail; Lammers, Jonas; Atzeni, Simone; Pandey, Cheeranjiv; Lütkewitte, Florian; Shirazi, Reza G.; Schlue, Fabian; Brecht, Benjamin; Rybkin, Vladimir V.; Stefszky, Michael; et al. (npj Quantum Information)
Simulating vibronic spectra is a central task in physical chemistry, offering insight into important properties of molecules. Recently, it has been experimentally demonstrated that photonic platforms based on Gaussian boson sampling (GBS) are capable of performing these simulations. However, whether an actual GBS approach is required depends on the molecule under investigation. To develop a better understanding on the requirements for simulating vibronic spectra, we explore connections between theoretical approximations in physical chemistry and their photonic counterparts. Mapping these approximations into photonics, we show that for certain molecules the GBS approach is unnecessary. We place special emphasis on the linear coupling approximation, which in photonics corresponds to sampling from multiple coherent states. By implementing this approach in experiments, we demonstrate improved similarities over previously reported GBS results for formic acid and identify the particular attributes that a molecule must exhibit for this, and other approximations, to be valid. These results highlight the importance in forming deeper connections between traditional methods and photonic approaches.

OAM-multiplexed holography via cascaded metasurfaces without post sampling and position multiplexing - Jin, Xiao; Zentgraf, Thomas (Metamaterials XV)

Engineering Disordered Many‐Particle Plasmonic Nanoclusters for Wafer‐Scale Uniform and Giant Electromagnetic Field Enhancement - Kim, Minjun; Devaraj, Vasanthan; Seo, Hyeon‐Seok; Eom, Seong‐Jae; Lee, Jeong‐Su; Lee, Donghan; Jeon, Min Yong; Zentgraf, Thomas; Lee, Jong‐Min (Laser & Photonics Reviews)
Scalable plasmonic technologies face a critical trade‐off: few‐body architectures offer high enhancement but are sensitive to fabrication flaws, while scalable methods like solid‐state dewetting yield large, low‐enhancement gaps. We introduce a paradigm shift using a many‐body plasmonic architecture inspired by statistical mechanics. By moving toward the continuum limit, local geometric variations are statistically averaged out, effectively decoupling optical performance from microscopic disorder. We implement this concept via a lithography‐ and etching‐free, multi‐step dewetting strategy, creating wafer‐scale nanoclusters. This process strategically forms a robust many‐body system by introducing numerous small satellite nanoparticles between larger particles. Crucially, this design achieves a high collective enhancement that surpasses even optimized few‐body systems, despite having larger individual gaps. Under optimized conditions, these substrates exhibit a surface‐enhanced Raman scattering enhancement factor approaching 4 × 10^8 with unprecedented reproducibility (RSD of ∼10%). This scalable, low‐cost concept establishes a practical route toward reproducible wafer‐scale nanophotonic platforms for sensing, spectroscopy, and quantum technologies.

High-gain effects in broadband continuous-wave parametric down conversion sources and measurements with undetected photons - Houde, Martin; Roeder, Franz; Silberhorn, Christine; Brecht, Benjamin; Quesada, Nicolás (New Journal of Physics)
Abstract We study theoretically how high-gain effects affect the measurement outcome of visible signal spectra in undetected photon measurement schemes. We consider two interferometric configurations: firstly, the SU(1,1) interferometer where the idler incurs loss and additional dispersion in between two identical, lossless, squeezers; secondly, the induced coherence interferometer where the idler incurs loss and additional dispersion in between two identical, lossless, squeezers and where the second squeezer is seeded by the idler and a vacuum ancilla mode. Furthermore, we consider a distributed loss configuration where the idler incurs loss as it propagates in the nonlinear medium. Motivated by experimental evidence and due to the fact that broadband sources are ideal for these measurement schemes, we use the dispersive data of a third-order dispersion engineered integrated waveguide parametric down conversion (PDC) source presented in Roeder et al (2024 New J. Phys. 26 123025) to model the PDC spectra in the three configurations. For each configuration we consider the case of idler-only (i) absorption, (ii) additional dispersion, and (iii) the combined effects. We obtain results which outline the strength and weaknesses of the different configurations at different operation points.

Quantum fisher information analysis for absorption measurements with undetected photons - Houde, Martin; Roeder, Franz; Silberhorn, Christine; Brecht, Benjamin; Quesada, Nicolás (Journal of Physics: Photonics)
Abstract We theoretically compare the quantum Fisher information (QFI) for three configurations of absorption spectroscopy with undetected idler photons: an SU(1,1) interferometer with inter-source idler loss, an induced-coherence (IC) setup in which the idler partially seeds a second squeezer together with a vacuum ancilla, and a distributed-loss (DL) scheme with in-medium attenuation. We calculate the QFI as a function of parametric gain for both full and signal-only detection access. For losses below 99% and low to moderate gain, the SU(1,1) configuration provides the largest QFI. At high gain and intermediate loss, the IC scheme performs best, while under extreme attenuation (transmission < 1%) the DL model becomes optimal. These results delineate the measurement regimes in which each architecture is optimal in terms of information theory.

Demonstration of a quantum C-NOT gate in a time-multiplexed fully reconfigurable photonic processor - Pegoraro, Federico; Held, Philip; Lammers, Jonas; Brecht, Benjamin; Silberhorn, Christine (Nature Communications)
The two-qubit controlled-not (C-NOT) gate is an essential component for gate-based quantum circuits. In fact, its operation, combined with single qubit rotations allows to realise any quantum circuit. Several strategies have been adopted in order to build quantum gates. Among them, photonics offers the dual advantage of excellent isolation from the environment and ease of manipulation at the single qubit level. Here we adopt a scalable time-multiplexed approach in order to build a fully reconfigurable architecture capable of implementing a post-selected C-NOT gate with a fidelity of (93.8 ± 1.4)%. We then show how our time-multiplexed platform can be employed to combine a C-NOT and a single qubit gate in order to generate the four Bell states.
Keywords: Photonic Quantum Computing; Time-multiplexing; Quantum Information

Spatially Uniform and Defect‐Tolerant Plasmonic Responses in 3D Printed Gold Nanoparticle Assemblies - Devaraj, Vasanthan; Kwak, Sunghyun; Kim, Hyeongjip; Sung, Sang‐Keun; Lee, Jong‐Min; Zentgraf, Thomas; Kim, Won‐Geun (Laser & Photonics Reviews)
Three‐dimensional (3D) assemblies of gold nanoparticles (AuNPs) offer a rich platform for plasmonic coupling and near‐field engineering, yet their optical behavior is often complex due to structural disorder and fabrication‐induced variability. Here, we present a systematic optical investigation of large‐scale 3D AuNP assemblies fabricated via meniscus‐guided assembly, focusing on the reproducibility, spatial uniformity, and mode evolution of their plasmonic responses. Spatially‐resolved dark‐field scattering measurements reveal that high‐aspect‐ratio AuNP pillars exhibit uniform scattering spectra along their height and across different pillars, despite variations in geometry and structure. Electromagnetic simulations suggest that this robustness arises from a collective many‐particle plasmonic response that remains optically active despite structural perturbations. The corresponding near‐field and surface‐charge distributions remain spatially distributed under representative structural perturbations, consistent with volumetric averaging across the three‐dimensional assembly. Building on this robust platform, we introduce compositional modulation through a core–satellite architecture by incorporating smaller AuNPs. This yields a composition‐dependent spectral redistribution, including the emergence of an additional long‐wavelength spectral feature in the core–satellite assemblies. Wavelength‐dependent surface‐enhanced Raman scattering measurements reveal contrasting responses under 633 and 785 nm excitation, reflecting redistribution of local plasmonic coupling pathways. These results provide process‐enabled guidelines for using meniscus‐guided 3D‐nanoprinting to realize robust nanoparticle assemblies.